Design of low complexity variable digital filters and reconfigurable filter banks for multi-standard wireless communication receivers - Sumit Jagdish Darak (2013)
Software defined radios (SDRs) and cognitive radios (CRs) empower mobile communication handsets to support multiple wireless communication standards and services, and improve the spectrum utilization efficiency. SDRs and CRs need multi-standard wireless communication receivers (MWCRs) to integrate existing as well as imminent communication standards into a single generic hardware platform. The limited reconfigurability of the analog front-end, sampling rate constraints of the currently available ADCs and extensive disparities between communication standards’ specifications, lead to the shifting of stringent channel(s) selection task to the digital front-end (DFE). Thus, the DFE needs either variable digital filters (VDFs) that provide variable lowpass (LP), highpass (HP), bandpass (BP) and bandstop (BS) responses and/or reconfigurable filter banks that provide independent and individual control over the bandwidth and the center frequency of subbands. Realizing such filters and filter banks with low area complexity, power consumption, group delay and reconfiguration delay is a challenging task. In this thesis, five VDFs and three reconfigurable filter banks have been proposed to address this research problem. The first work is a low complexity reconfigurable filter bank based on the coefficient decimation method (CDM) and frequency response masking (FRM) (termed as CDM-FRM filter bank). It offers coarse control over the bandwidth and the center frequency of subbands. In the next work, a linear phase VDF based on modified second order frequency transformation (termed as MFT-VDF) have been proposed. The MFT-VDF, with wide cut-off frequency range, overcomes the constraint of limited cut-off frequency range in existing VDFs and also provides variable LP, HP, BP and BS responses from av fixed-coefficient prototype filter. Using the MFT-VDF, a reconfigurable fast filter bank (RFFB) has been proposed which offers an unabridged control over subband bandwidths on a desired range, compared to the coarse control in the CDM-FRM filter bank. It also provides fine control over the center frequency of fixed bandwidth subbands which is useful in scenarios where channels have fixed bandwidth but varying center frequencies. The implementation complexity of the filter banks can be reduced significantly if its resolution is independent of the channel bandwidth and is equal to the number of channels concurrently handled by subsequent digital signal processing algorithms. To achieve this, a filter bank which provides independent and individual control over the bandwidth and the center frequency of subbands is desired. With this goal, a new low complexity and reduced delay VDF and reconfigurable filter bank have been proposed. The linear phase VDF is designed by combining new modified CDM (MCDM) in [29] with spectral parameter approximation (SPA) (termed as SPA-MCDM VDF) while non-linear phase VDF is designed by combining the MCDM with allpass transformation (APT) (termed as APT-MCDM VDF). Both these VDFs provide variable LP, HP, BP and BS responses over entire Nyquist band and offer substantial savings in gate counts over existing VDFs. The non-linear phase APT-MCDM VDF requires less gate counts than the linear phase VDFs and is suitable for energy detection based spectrum sensing. A new APT-VDF obtained by combining first and second order APT with the CDM has been proposed which requires even less gate count than the APT-MCDM VDF. The linear phase SPA-MCDM filter bank designed using the SPA-MCDM VDF allows independent and individual control over the bandwidth and center frequencies of subbands. The gate count and group delay comparisons show that the SPA-MCDM filter bank is superior compared to other filter banks. China's construction industry is huge. As in 1988, it employs more than 25 million people. It has an annual output of about 286.1 billion yuan (or US$64 billion in the same year) and accounts for 9.8% of GDP. It has been growing at an average rate of 18% since 1979. The high growth rate indicates extreme shortage of physical infrastructure in the country and is likely to continue for many years.